Bayan nila pilipino culture nights and student performance at home in Southern California. - Matherne, Neal (Asian Studies, 2013)
In this work, I interpret Filipina/o-American cultural production and question the bounded nature of ethnomusicology, area studies, ethnic studies, and cultural anthropology. I describe the challenges of ethnographic research on music and performance at “home” in Southern California among college students, who take part in a Pilipino Culture Night (PCN). PCN performers strategically manipulate the symbols of homeland (both the Philippines and the U.S.) through singing, playing instruments, acting, and dancing. I interpret this practice by drawing on existing literature on Asian-American performance and identifying key critical discourses in Filipina/o-American performance offered by the PCN model.